DEAD-ly Affairs: The Roles of DEAD-Box Proteins on HIV-1 Viral RNA Metabolism - Rao, Shringar; Mahmoudi, Tokameh (Frontiers in Cell and Developmental Biology, 2022)
In order to ensure viral gene expression, Human Immunodeficiency virus type-1 (HIV-1) recruits numerous host proteins that promote optimal RNA metabolism of the HIV-1 viral RNAs (vRNAs), such as the proteins of the DEAD-box family. The DEAD-box family of RNA helicases regulates multiple steps of RNA metabolism and processing, including transcription, splicing, nucleocytoplasmic export, trafficking, translation and turnover, mediated by their ATP-dependent RNA unwinding ability. In this review, we provide an overview of the functions and role of all DEAD-box family protein members thus far described to influence various aspects of HIV-1 vRNA metabolism. We describe the molecular mechanisms by which HIV-1 hijacks these host proteins to promote its gene expression and we discuss the implications of these interactions during viral infection, their possible roles in the maintenance of viral latency and in inducing cell death. We also speculate on the emerging potential of pharmacological inhibitors of DEAD-box proteins as novel therapeutics to control the HIV-1 pandemic.